Potential Zoonotic Faecal Bacteria from Sunda Porcupine (Hystrix javanica) and Their Antimicrobial Resistance Profiles - Sarsa Nisa; Rifka A. Safitri; Nurul Inayah; Achirul Nditasari; Susiana Purwantisari; Rejeki Ferniah; Anang Achmadi; Taufiq Nugraha; Sugiyono Saputra (Microbiology Indonesia, 2021)
Sunda porcupine (Hystrix javanica) is one of the Indonesian endemic species which is often sought after for their meat. Although it is becoming increasingly popular for extreme culinary, information regarding biological risks arising from this wildlife is very limited. This study aimed to assess potential zoonotic faecal bacteria carried by Sunda porcupine with culture-dependant approach and to investigate whether antimicrobial resistant isolates can be found in wildlife. A total 22 faecal samples were collected from captive Sunda porcupine and tested for the presence of pathogens in selective media for Salmonella and Listeria. After inoculating the samples in Rappaport-Vassiliadis (RV) Salmonella enrichment broth, two samples (9%) were regarded as positive for Salmonella in this presumptive test which indicated by growth black colonies on xylose lysine deoxycholate (XLD) agar. Meanwhile, the presence for Listeria was presumptively positive in all samples (100%), indicated by black colour appearance in Listeria isolation transwab. In total, 38 bacterial isolates were successfully purified, preserved and subjected for antimicrobial susceptibility testing (AST) by disk diffusion method. Resistance to ceftriaxone (3rd generation cephalosporins) was not detected while resistance to one or two antimicrobials was observed in seven isolates. Further, 16S rRNA bacterial identification was performed for selected isolates and based on sequence similarity on GenBankÂ® databases and phylogenetic tree construction, those isolates were denoted as Pseudomonas xinjiangensis (XG4.4), Shigella sonnei (XD8.2 and G11.3), Proteus mirabilis (XH3.3, H4.2, and E1.2) and Klebsiella quasipneumoniae subsp. similipneumoniae (XF4.2). All identified isolates were sensitive to amikacin, amoxicillin-clavulanic acid, cefoxitin and ceftriaxone, except for one isolate Shigella sonnei (XD8.2) which was resistant to cefoxitin. Further research to confirm the pathogenicity of the isolates is still needed but based on these results, we support the hypothesies that Sunda porcupine is potential as a reservoir pathogenic bacteria and preventive measures are crucial to prevent transmission when processing this bushmeat.